Substantiation of Drying Modes for a New Universal Method of Short Flax Fiber Drying - E. V. Novikov; I. N. Altukhova; E. N. Koroleva; A. V. Bezbabchenko (Сельскохозяйственные машины и технологии, 2024)
Deep processing enterprises often receive short flax fibers with high moisture content, which must be dried to meet processing requirements. (Research purpose) To investigate the effect of process parameters (speed, drying agent consumption, air injection and vacuum, air temperature in the drying chamber) on the drying time of short and uniform flax fibers. (Materials and methods) The studies were conducted using a new drying unit with air recirculation. Flax fibers were pre-moistened to a moisture content of 35-40 percent and loaded into the working chamber. Before drying, and then at one-minute intervals during the process, the fibers were weighed to monitor moisture loss. Additionally, the air temperature at the inlet and the outlet of the drying chamber, as well as in the mixing chamber, was measured before the start of the process and then at one-minute intervals. Experiments were conducted using various combinations of speed and flow rates for both incoming and outgoing air in the drying chamber. The initial temperature of the drying agent was 70-80 degrees Celsius, with a relative humidity of 5 percent. The average ambient temperature in the facility was 17 degrees Celsius, and the recirculation degree was 1.4. (Results and discussion) The drying duration of short flax fibers from a moisture of 30 to 14 percent is 1.3-1.9 minutes. Switching the airflow mode from injection to vacuum does not significantly affect the drying time; for effective drying, an air speed of 8-9 meters per second should be maintained. The temperature of the drying agent continuously increases, while the exhaust air temperature initially drops by 25-28 degrees Celsius before rising again. The temperature of the mixed air remains almost unchanged. (Conclusions) For the first time, optimal process parameters have been determined for drying short flax fibers in a new installation with air recirculation: a drying duration of 1.3-1.4 minutes, a drying agent temperature of 75-80 degrees Celsius, as well as ideal combinations of airflow rate and speed for both the incoming and outgoing air.